MATHEMATICAL MODELING APPLIED TO THE ANALYSIS OF MAGMATIC INTRUSIONS THERMAL INFLUENCE IN PARANÁ BASIN - Oliveira, Bruno Rodrigues de; Corval, Artur; Valente, Sergio de Castro; Lambert, Wanderson José; Miranda, Alan Wanderley Albuquerque; Oliveira, Luiz Gabriel Souza de; Fernandes, Victor Hugo (Boletim Paranaense de Geociências, 2022)
This paper has the objective to present equations capable of generating one-dimensional models that permit to quantify the thermal influence caused by igneous intrusions. In Paraná Basin, the petroleum systems were great influenced by igneous activities in which they are presented by a thick lava effusion, large number of dykes in the entire sedimentary section and various levels of sills intruded in stratifications to provide thermal energy for organic maturation. Thus, a better understanding of how and how much the intrusions affect the generation of oil and gas is extremely necessary since the knowledge related to the effects of intrusions in such atypical petroleum system is still insufficient. The obtained results show: the thermal influence caused by igneous intrusions is much higher than that proposed in the literature; the greater the number of intrusions and the thicker they are, the thermal influence is unfavorable at short distances and favorable at large distances.